Towards a socially just model: balancing hunger and response to the COVID-19 pandemic in Bangladesh - Rashid, Sabina Faiz; Theobald, Sally; Ozano, Kim (BMJ Global Health 2020, 2020)
This article was published in the MJ Global Health 2020 [ © 2020 Author(s) (or their employer(s)). ] and the definitive version is available at: http://dx.doi.org/10.1136/bmjgh-2020-002715. The Journal's website is at: https://gh.bmj.com/content/5/6/e002715